Menaquinone-4 protects CD8+ T cells from ferroptosis to enhance anti-tumor immunity - Jiarong Wang; Wen Wang; Simiao Fan; Liyun Liang; Huaibin Hu; Zenqing Song; Yu Zhang; Jiamei Zhang; Wanying Xiao; Biyu Zhang; Yaxin Li; Liang Luo; et al. (Science China Life Sciences, 2026)

Economic rhythms and green tides: Charting China's dual dividends through synergistic policies - Yu-Jie Hu; Rui Zhang; Ailing Luo; Yu Hao (Environmental Impact Assessment Review, 2026)

Characterization of the pathogenicity of newly emerged NADC30-Like PRRSV strains causing severe brain infections via twice inter-lineage recombination - Yuan Yang; Cheng Luo; Yixue Yan; Haoyu Chen; Feimin Xie; Ziyi Wang; Wei Wei; Mingsheng Cen; Xinyue Chen; Wenlin Huang; Xin Lan; Yu Feng; et al. (Veterinary Microbiology, 2026)

Development of an online near-infrared spectroscopic method for monitoring moisture and particle size of traditional Chinese medicine tablet granules in the feed frame - Zihao Zhang; Zhijian Zhong; Qingmin Meng; Xingnan Zhao; Yao Zhang; Ailing Zhang; Yilin Luo; Xiaojian Luo; Xiaoyong Rao; Wei Liu (Next Research, 2026)

Reducing chalkiness and enhancing quality and yield in hybrid indica rice at the middle panicle position through optimal water and nitrogen management - Yuanyuan Sun; Xiaojuan Yuan; Yinghan Luo; Guanzhou Luo; Kun Chen; Ailing Wang; Mingming Hu; Zongkui Chen; Zhiyuan Yang; Jun Ma; Yongjian Sun (Food Chemistry, 2025)

The role of BTG2/PI3K/AKT pathway-mediated microglial activation in T-2 toxin-induced neurotoxicity - Xiukuan Li; Jinyun Long; Chunyan Yao; Xiaoling Liu; Na Li; Yumeng Zhou; Dawei Li; Guiyuan Xiong; Kexue Wang; Yuhui Hao; Ka Chen; Ziyuan Zhou; et al. (Toxicology Letters, 2024)

Exploring competitiveness of taxis to ride-hailing services from a multidimensional spatio-temporal perspective: A case study in Beijing, China - Yihao Luo; Ailing Huang; Zhengbing He; Jiaqi Zeng; Dianhai Wang (Journal of Transport Geography, 2024)

Microbial community structure in a constructed wetland based on a recirculating aquaculture system: Exploring spatio-temporal variations and assembly mechanisms - Wenjie Tian; Qiufen Li; Zijun Luo; Chao Wu; Bo Sun; Danting Zhao; Saisai Chi; Zhengguo Cui; Ailing Xu; Zhiwen Song (Marine Environmental Research, 2024)

Identification and functional characterization of REGULATORY PARTICLE NON-ATPASE 1a-like (AhRPN1a-like) in peanuts during aluminum-induced programmed cell death - Guoting Liao; Shuzhen Luo; Xinyue Li; Ailing Li; Yunchuan Mo; Aiqin Wang; Dong Xiao; Long-Fei He; Jie Zhan (Journal of Plant Physiology, 2023)

The Predicted Model of the Sensory Quality of Refrigerated Tilapia Skin Established Based on Characteristic Near-Infrared Spectrum - Huawei Ma; Min Lv; Zhide Ruan; Fariha Latif; Chuanyan Pan; Xu Luo; Qiong Yang; Xiaobao Qi; Yuan Zhong; Ailing Guo (Journal of Aquatic Food Product Technology, 2023)

Development of β-elemene and Cisplatin Co-Loaded Liposomes for Effective Lung Cancer Therapy and Evaluation in Patient-Derived Tumor Xenografts - Mingxiang Cao; Mengmeng Long; Qiuping Chen; Yapeng Lu; Qianqian Luo; Yue Zhao; Ailing Lu; Cunwang Ge; Li Zhu; Zhongping Chen (Pharmaceutical Research, 2019)

Creation of miniature pig model of human Waardenburg syndrome type 2A by ENU mutagenesis - Tang Hai; Weiwei Guo; Jing Yao; Chunwei Cao; Ailing Luo; Meng Qi; Xianlong Wang; Xiao Wang; Jiaojiao Huang; Ying Zhang; Hongyong Zhang; Dayu Wang; et al. (Human Genetics, 2017)

Genetic diversity and evolutionary characteristics of type 2 porcine reproductive and respiratory syndrome virus in southeastern China from 2009 to 2014 - Jiankui Liu; Xia Zhou; Junqiong Zhai; Bing Li; Chunhua Wei; Ailing Dai; Xiaoyan Yang; Manlin Luo (Archives of Virology, 2017)

Short-term exposure to particulate air pollution and risk of myocardial infarction: a systematic review and meta-analysis - Chunmiao Luo; Xiaoxia Zhu; Cijiang Yao; Lijuan Hou; Jian Zhang; Jiyu Cao; Ailing Wang (Environmental Science and Pollution Research, 2015)

Microarray data uncover the genome-wide gene expression patterns in response to heat stress in rice post-meiosis panicle - Xianwen Zhang; Hairong Xiong; Ailing Liu; Xiaoyun Zhou; Yan Peng; Zhuoxue Li; Guangyu Luo; Xiangrong Tian; Xinbo Chen (Journal of Plant Biology, 2014)

Heat shock factor OsHsfB2b negatively regulates drought and salt tolerance in rice - Jianhua Xiang; Jing Ran; Jie Zou; Xiaoyun Zhou; Ailing Liu; Xianwen Zhang; Yan Peng; Ning Tang; Guangyu Luo; Xinbo Chen (Plant Cell Reports, 2013)

Effects of litter quality and climate change along an elevation gradient on litter mass loss in an alpine meadow ecosystem on the Tibetan plateau - Guangping Xu; Yigang Hu; Shiping Wang; Zhenhua Zhang; Xiaofeng Chang; Jichuang Duan; Caiyun Luo; Zengguo Chao; Ailing Su; Qiaoyan Lin; Yingnian Li; Mingyuan Du (Plant Ecology, 2010)

Temperature sensitivity of nutrient release from dung along elevation gradient on the Qinghai–Tibetan plateau - Guangping Xu; Zengguo Chao; Shiping Wang; Yigang Hu; Zhenghua Zhang; Jichuang Duan; Xiaofeng Chang; Ailing Su; Caiyun Luo; Yingnian Li; Mingyuan Du (Nutrient Cycling in Agroecosystems, 2010)

Effect of warming and grazing on litter mass loss and temperature sensitivity of litter and dung mass loss on the Tibetan plateau - CAIYUN LUO; GUANGPING XU; ZENGGUO CHAO; SHIPING WANG; XINGWU LIN; YIGANG HU; ZHENHUA ZHANG; JICHUANG DUAN; XIAOFENG CHANG; AILING SU; YINGNIAN LI; XINQUAN ZHAO; et al. (Global Change Biology, 2010)
Knowledge about the role of litter and dung decomposition in nutrient cycling and response to climate change and grazing in alpine ecosystems is still rudimentary. We conducted two separate studies to assess the relative role of warming and grazing on litter mass loss and on the temperature sensitivity of litter and dung mass loss. Experiments were conducted for 1–2 years under a controlled warming–grazing system and along an elevation gradient from 3200 to 3800 m. A free‐air temperature enhancement system (FATE) using infrared heaters and grazing significantly increased soil temperatures (average 0.5–1.6 °C) from 0 to 40 cm depth, but neither warming nor grazing affected soil moisture except early in the growing seasons at 30 cm soil depth. Heaters caused greater soil warming at night‐time compared with daytime, but grazing resulted in greater soil warming during daytime compared with night‐time. Annual average values of the soil temperature at 5 cm were 3.2, 2.4 and 0.3 °C at 3200, 3600 and 3800 m, respectively. Neither warming nor grazing caused changes of litter quality for the first year of the controlled warming–grazing experiment. The effects of warming and grazing on litter mass losses were additive, increasing litter mass losses by about 19.3% and 8.3%, respectively, for the 2‐year decomposition periods. The temperature sensitivity of litter mass losses was approximately 11% °C −1 based on the controlled warming–grazing experiment. The annual cumulative litter mass loss was approximately 2.5 times that of dung along the elevation gradient. However, the temperature sensitivity (about 18% °C −1 ) of the dung mass loss was about three times that of the litter mass loss. These results suggest greater warming at night‐time compared with daytime may accelerate litter mass loss, and grazing will enhance carbon loss to atmosphere in the region through a decrease of litter biomass and an increase of dung production with an increase of stocking rate in future warmer conditions.